PENGARUH PEMBERIAN FILTRAT DAUN KATUK (SAUROPUS ANDROGYNUS) TERHADAP GAMBARAN HISTOPATOLOGI PARU MENCIT YANG TERPAPAR ASAP ROKOK - YANTI TOGATOROP, ELZASS (Universitas Negeri Surabaya, 2013)
Research has been conducted to prove that the katuk leaves filtrate can reduce the level of damage lung tissue. Sixty male mice as a subject divided into 5 groups; K0 (normal control), K1 (exposed by cigarette smoke control), P1 (exposed by cigarrete smoke and given katuk leaves filtrate 2 ml/100 gBW/day), P2 (exposed by cigarette smoke and given katuk leaves filtrate 2.5 ml/100 gBW/day), and P3 (exposed by cigrette smoke and given katuk leaves filtrate 3 ml/100 gBW/day). The cigarette smoke exposed by 1 piece smoke/1,5 hour/day. The results of the study showed the level of lung tissue damage with a value of significance (p-value<α 0,05) congestion (0,058), inflammation  (0,314), degeneration (0,366), necrosis (0,731), and total damage (0,788). It can be conclude the katuk filtrate leaves can’t repair lung tissue damage of exposure to cigarette smoke.   Key words: cigarette smoke; katuk leaves; antioxidant; lung tissue damage